Control of quantum systems : theory and methods - Cong, Shuang (Singapore : John Wiley & Sons Inc., 2014)
"Control of Quantum Systems: Theory and Methods provides an insight into the modern approaches to control of quantum systems evolution, with a focus on both closed and open (dissipative) quantum systems. The topic is timely covering the newest research in the field, and presents and summarizes practical methods and addresses the more theoretical aspects of control, which are of high current interest, but which are not covered at this level in other text books. The quantum control theory and methods written in the book are the results of combination of macro-control theory and microscopic quantum system features. As the development of the nanotechnology progresses, the quantum control theory and methods proposed today are expected to be useful in real quantum systems within five years. The progress of the quantum control theory and methods will promote the progress and development of quantum information, quantum computing, and quantum communication"--
"Control of Quantum Systems: Theory and Methods provides an insight into the modern approaches to control of quantum systems evolution, with a focus on both closed and open (dissipative) quantum systems"--
Chapter 9: Manipulation Methods of the General State9.1 Quantum System Schmidt Decomposition and its Geometric Analysis; 9.2 Preparation of Entanglement States in a Two-Spin System; 9.3 Purification of the Mixed State for Two-Dimensional Systems; References; Chapter 10: State Control of Open Quantum Systems; 10.1 State Transfer of Open Quantum Systems with a Single Control Field; 10.2 Purity and Coherence Compensation through the Interaction between Particles; Appendix 10.A Proof of Equation 10.59; References; Chapter 11: State Estimation, Measurement, and Control of Quantum Systems
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Quantum systems -- Automatic control; Control theory; Control theory; Quantum systems -- Automatic control; TECHNOLOGY & ENGINEERING -- Quality Control; Electronic books